New Apostolic Reformation: Apostolic Ministry for Today - Ervin Budiselić (Kairos (English Ed.))
This article analyzes the idea of Peter Wagner, the main representative of the New Apostolic Reformation, that apostles should and must govern local church congregations. The support for this claim is based primarily on Ephesians 2:20 where Paul said that the church is “built on the foundation of the apostles and prophets.” The question then is, whether people with the gift of apostolic ministry represent that foundation or the foundation is the apostolic teaching itself. Closely connected with this is the question whether the apostolic ministry/office continues today or not. The first part of the article analyzes the reasons for the occurrence of this idea in Wagner’s theology and the ultimate goals of the NAR movement. In the second part, it analyzes the biblical understanding of the apostolic ministry which is common for NAR theologians, and finally, compares these ideas with traditional ideas about apostolic ministry in Christianity. The author argues that while apostolic ministry in the Body of Christ continues even today and should be recognized as an office, the authority of apostles should be influential and spiritual, not governmental and hierarchical.